Penguatan Pendidikan Karakter Nilai Integritas melalui Hizbul Wathan di Sekolah Dasar Muhammadiyah Karangkajen - Suyitno, Suyitno; S, Jihan Amalia (Universitas Muhammadiyah Magelang, 2025)
The purpose of this study was to describe the strengthening of integrity character education in Hizbul Wathan extracurricular at SD Muhammadiyah Karangkajen Yogyakarta. This type of research is a qualitative research with a case study approach. The subjects of this study were school principals, PPK coordinators, activity coordinators, Hizbul Wathan coaches, and students. The object of research is the PPK on the value of integrity in Hizbul extracurriculars. Collecting data through observation, interview, and documentation techniques. The validity of the data using triangulation techniques and data sources. Data analysis using the Miles and Hubermen model consists of data reduction, data presentation, and drawing conclusions. The results showed that the strengthening of character education on the value of integrity in Hizbul Wathan extracurricular activities, namely, 1) Strengthening of integrity character education has been instilled in students by the coaches adjusted to the Hizbul Wathan curriculum. 2) The strategy carried out by the coach to increase the strengthening of character education for the value of integrity is by providing direct examples during activities, with the Al Ihsan strategy, and by increasing understanding, experience, and knowledge to students.